Co-operative roles for DNA supercoiling and nucleoid-associated proteins in the regulation of bacterial transcription - DORMAN, CHARLES (My University, 2013)
DNA supercoiling and NAPs (nucleoid-associated proteins) contribute to the regulation of transcription of many bacterial genes. The horizontally acquired SPI (Salmonella pathogenicity island) genes respond positively to DNA relaxation, they are activated and repressed by the Fis (factor for inversion stimulation) and H-NS (histone-like nucleoid-structuring) NAPs respectively, and are positively controlled by the OmpR global regulatory protein. The ompR gene is autoregulated and responds positively to DNA relaxation. Binding of the Fis and OmpR proteins to their targets in DNA is differentially sensitive to its topological state, whereas H-NS binds regardless of the topological state of the DNA. These data illustrate the overlapping and complex nature of NAP and DNA topological contributions to transcription control in bacteria.
PUBLISHED
Keywords: transcription; nucleoid-associated protein; DNA supercoiling; DNA gyrase; bacterial transcription; Genes & Society; Immunology, Inflammation & Infection